Dietary Pattern of Garlic and Risk of Chronic Diseases: Evidence From Three Large‐Scale Cohorts - Xiaoyu Tai; Tao Luo; Keying Song; Hui Zhao; Silu Chen; Huiqin Li; Min Liu; Jianghong Dai; Xu Qian; Mulong Du (Health Care Science)
ABSTRACT Background Understanding the relationship between garlic and chronic diseases could help to improve prevention and reduce the burden of diseases. This study aimed to examine the association between garlic consumption and the risk of chronic diseases. Methods We included 26,524 participants from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) with data of the frequency of garlic consumption, 7658 participants from the Xinjiang multiethnic cohort (XMC) study with data of garlic intake, and 141,684 participants from the UK Biobank (UKBB) with data of the preference for garlic. The dietary pattern of garlic, including the frequency of consuming garlic, garlic intake, and garlic preference information, was collected using a food questionnaire for each cohort. Logistic regression and structural equation modeling were used to assess the effect of garlic consumption on five common chronic diseases, which comprised cancer, diabetes, hypertension, respiratory diseases, and cardiovascular disease (CVD). Results In the CLHLS cohort, individuals who consumed garlic almost every day had a significantly lower risk of five of the most common chronic diseases (cancer: odds ratio [OR] = 0.51, 95% confidence interval [CI] = 0.30–0.81, p = 0.006; diabetes: OR = 0.58, 95% CI = 0.43–0.76, p < 0.001; hypertension: OR = 0.68, 95% CI = 0.61–0.77, p < 0.001; respiratory diseases: OR = 0.77, 95% CI = 0.67–0.87, p < 0.001; and CVD: OR = 0.69, 95% CI = 0.59–0.80, p < 0.001). Similarly, in the XMC, there was a consistent protective effect of high garlic intake on hypertension, respiratory diseases and CVD. Additionally, in the UKBB cohort, individuals who liked garlic had a decreased risk of diabetes and CVD. Notably, in three cohorts, structural equation modeling results showed that there was a significant protective total effect of garlic consumption on the five common chronic diseases. Conclusions A high garlic consumption is associated with a reduced risk of chronic diseases. Our findings highlight the potential protective role of garlic in preventing chronic diseases.